Comparative Analysis of Homologous Sequences of Saccharum officinarum and Saccharum spontaneum Reveals Independent Polyploidization Events - Sharma, Anupma; Song, Jinjin; Lin, Qingfan; Singh, Ratnesh; Ramos, Ninfa; Wang, Kai; Zhang, Jisen; Ming, Ray; Yu, Qingyi (Frontiers in Plant Science, 2018)
Sugarcane (Saccharum spp. hybrids) is an economically important crop widely grown in tropical and subtropical regions for sugar and ethanol production. However, the large genome size, high ploidy level, interspecific hybridization and aneuploidy make sugarcane one of the most complex genomes and have long hampered genome research in sugarcane. Modern sugarcane cultivars are derived from interspecific hybridization between S. officinarum and S. spontaneum with 80-90% of the genome from S. officinarum and 10-20% of the genome from S. spontaneum. We constructed bacterial artificial chromosome (BAC) libraries of S. officinarum variety LA Purple (2n=8x=80) and S. spontaneum haploid clone AP85-441 (2n=4x=32), and selected and sequenced 97 BAC clones from the two Saccharum BAC libraries. A total of 5,847,280 bp sequence from S. officinarum and 5,011,570 bp from S. spontaneum were assembled and 749 gene models were annotated in these BACs. A relatively higher gene density and lower repeat content were observed in S. spontaneum BACs than in S. officinarum BACs. Comparative analysis of syntenic regions revealed a high degree of collinearity in genic regions between Saccharum and Sorghum bicolor and between S. officinarum and S. spontaneum. In the syntenic regions, S. spontaneum showed expansion relative to S. officinarum, and both S. officinarum and S. spontaneum showed expansion relative to sorghum. Among the 75 full-length LTR retrotransposons identified in the Saccharum BACs, none of them are older than 2.6 mys and no full-length LTR elements are shared between S. officinarum and S. spontaneum. In addition, divergence time estimated using a LTR junction marker and a syntenic gene shared by 3 S. officinarum and 1 S. spontaneum BACs revealed that the S. spontaneum intergenic region was distant to those from the 3 homologous regions in S. officinarum. Our results suggested that S. officinarum and S. spontaneum experienced at least two rounds of independent polyploidization in each lineage after their divergence from a common ancestor.